International Conference on Computing, Communication &Amp; Automation 2015
DOI: 10.1109/ccaa.2015.7148561
|View full text |Cite
|
Sign up to set email alerts
|

Classification of heart diseases from ECG signals using wavelet transform and kNN classifier

Abstract: Heart is the most vital organ which circulates blood along with nutrients and oxygen throughout the body. There are number of reasons which may affect its normal working. In this paper ten heart diseases, as well as normal, have been classified by extracting features from original ECG (electrocardiogram) signals and sixth level wavelet transformed ECG signals. The results have been compared and improved accuracy has been obtained using wavelet transformed signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…The usage of wavelet-compressed data from the St. Petersburg Institute of Cardiological Technics 12lead arrhythmia database was our first step. In general, the MIT-BIH arrhythmia database is used by most research that is performed on ECG signals [1][2][3][4][5][6][7][8][9][10][11][12]14,16,19,[21][22][23]25,26], and classification is executed on a single channel [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][21][22][23][24][25][26][27]. Our research was performed on 12 channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The usage of wavelet-compressed data from the St. Petersburg Institute of Cardiological Technics 12lead arrhythmia database was our first step. In general, the MIT-BIH arrhythmia database is used by most research that is performed on ECG signals [1][2][3][4][5][6][7][8][9][10][11][12]14,16,19,[21][22][23]25,26], and classification is executed on a single channel [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][21][22][23][24][25][26][27]. Our research was performed on 12 channels.…”
Section: Discussionmentioning
confidence: 99%
“…The SVM [4,5,8,14,16,18,21,22,24] is another popular technique for classification of arrhythmia. Random forest [9], linear classifier [10], morphology consistency evaluation [13], cluster and centroid identification [15], linear discriminant analysis [17], threshold based classifier [20], KNN [7,23], and naive Bayes [26] are the other classification methods that are used in related works. The results obtained from 12-lead ECG recordings using bagged trees classification showed that our performance was as successful as others and more stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although feature methodology tries to quantify ECG in a discriminative way, the heuristics of hand-crafting process and the complicated variation of signals unavoidably impede the performance enhancement. Therefore, pattern analysis and/or machine learning techniques play an important role in further improving the classification performance based on the extracted features [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, para la detección y clasificación de etapas de sueño a partir del ECG (Yilmaz et al, 2010) y para la detección de períodos de apnea en combinación con AdaBoost Bootstrap (Kao et al, 2012). También se ha usado KNN para diagnosticar enfermedades del corazón de forma automática (Saini et al, 2015).…”
Section: Introductionunclassified